Mathematics Anxiety in Online Mathematics Learning - Dara Suci Munggaran; Tika Karlina Rachmawati; Wildatus Sholihah (Gunung Djati Conference Series, 2022)
Mathematics anxiety is one of the problems with online mathematics learning. Mathematics anxiety is affected by both the student and the outside factors. Developing symptoms of mathematical anxiety in students is highly concerning because it can result in inadequate online mathematics learning. The purpose of this study was to describe mathematical anxiety in online mathematics learning. The method used by researchers is the approach to literature studies. Besides the results of previous studies regarding mathematics anxiety in online mathematics learning, it can be known that mathematical anxiety affects the results and achievement of learning mathematics and affects student's mathematical abilities. So that teachers and parents need to have knowledge about the symptoms of mathematical anxiety in order to have strategies for overcoming and minimizing mathematical anxiety experienced by students.